Influence of Total Population Against Poverty Numbers Using Linear Regression Method in Jakarta - Jeffry Lingau (Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of population on poverty rates in Jakarta during the 2017-2022 period. The analytical tool used was simple regression. The results reveal that population does have a lasting effect on poverty rates in Jakarta during 2017-2022.